2015
DOI: 10.1177/0021998315584650
|View full text |Cite
|
Sign up to set email alerts
|

A new higher order analysis model for sandwich plates with flexible core

Abstract: A new kind of higher order analysis model is presented for sandwich plates with flexible core, especially ''soft'' core. The governing equations derived from equilibrium differential equations of motions are analytically solved for simply supported sandwich plate with a flexible core. The Navier-type solutions for free vibration analysis and static bending are presented for sinusoidal and uniformly distributed loads. The accuracy and convergence of the present theory and solution are ascertained by comparing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The amount of composite and composite structures used in the latest NH-90 European ‘Tiger’ helicopter up to 80% [3]. Mechanical properties of sandwich plates with homogenous and functionally graded material core should be investigated carefully for maritime, offshore and civil engineering application in long-span lightweight structures [46]. One of the major problems in sandwich structure is abrupt change in material properties across interfaces between the skins and the core, which can result in large interlaminar stresses, often appearing in local or global delaminations.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of composite and composite structures used in the latest NH-90 European ‘Tiger’ helicopter up to 80% [3]. Mechanical properties of sandwich plates with homogenous and functionally graded material core should be investigated carefully for maritime, offshore and civil engineering application in long-span lightweight structures [46]. One of the major problems in sandwich structure is abrupt change in material properties across interfaces between the skins and the core, which can result in large interlaminar stresses, often appearing in local or global delaminations.…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of 3D analysis, Teo and Liew [26] found that a method called differential quadrature (DQ) can effectively analyze rectangular orthotropic plates which have the boundary conditions of SSSS, SCCC, CSSS, and CCCC. Tian et al [27,28] proposed a new higher order analysis model for sandwich and FGM plates with flexible core and obtained the fundamental frequencies and static bending under sinusoidal and uniformly distributed loads. A semianalytical method is employed to analyze free vibration behaviors of composite laminated doubly curved, cylindrical, and spherical shells by Li et al [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties of sandwich plates with a homogeneous and functionally graded material core have been investigated in the area of long-span lightweight structures [1,2,3,4]. Theoretical models, such as shear deformation plate theory, energy method, finite element method, and three-dimensional elastic theory, have been used to investigate the mechanical behavior of FGM structures.…”
Section: Introductionmentioning
confidence: 99%